Development of a pathogenesis‐based therapy for peeling skin syndrome type 1. (2nd November 2020) - Valentin, F.; Wiegmann, H.; Tarinski, T.; Nikolenko, H.; Traupe, H.; Liebau, E.; Dathe, M.; Oji, V.
Summary: Background: Peeling skin syndrome type 1 (PSS1) is a rare and severe autosomal recessive form of congenital ichthyosis. Patients are affected by pronounced erythroderma accompanied by pruritus and superficial generalized peeling of the skin. The disease is caused by nonsense mutations or complete deletion of the CDSN gene encoding for corneodesmosin (CDSN). PSS1 severely impairs quality of life and therapeutic approaches are totally unsatisfactory. Objectives: The objective of this study was to develop the first steps towards a specific protein replacement therapy for CDSN deficiency. Using this approach, we aimed to restore the lack of CDSN and improve cell–cell cohesion in the transition area of the stratum granulosum (SG) to the stratum corneum. Methods: Human CDSN was recombinantly expressed in Escherichia coli . A liposome‐based carrier system, prepared with a cationic lipopeptide to mediate the transport to the outer membrane of keratinocytes, was developed. This formulation was chosen for CDSN delivery into the skin. The liposomal carrier system was characterized with respect to size, stability and toxicity. Furthermore, the interaction with primary keratinocytes and human epidermal equivalents was investigated. Results: The liposomes showed an accumulation at the membranes of keratinocytes. CDSN‐deficient epidermal equivalents that were treated with liposomal encapsulated CDSN demonstrated presence of CDSN in the SG. Finally, the penetration assay and histological examinations revealed an improved epidermal integrity for CDSN‐deficient epidermal equivalents, if they were treated with liposomal encapsulated CDSN. Conclusions: This study presents the first preclinical in vitro experiments for a future specific protein replacement therapy for patients affected by PSS1. Abstract : What is already known about this topic? Peeling skin syndrome type 1 (PSS1) refers to Mendelian disorders of cornification and is characterized by pruritus, pronounced erythroderma with skin abnormalities and lifelong patchy peeling of the skin. The disease is caused by autosomal recessive nonsense mutations in the gene encoding corneodesmosin (CDSN). Histopathologically, the absence of CDSN is characterized by subcorneal splitting and enhanced detachment of corneocytes. What does this study add? We present a liposomal formulation, which can be used for topical delivery of recombinant CDSN. Our in vitro study shows that the impaired barrier of CDSN‐deficient human epidermal equivalents can be improved when treated with liposomal human CDSN. What is the translational message? This study presents, for the first time, preclinical in vitro experiments for a specific protein replacement therapy in patients with PSS1. Linked Comment: Schmuth. Br J Dermatol 2021; 184 :998–999 .